Identifying and Developing Musical Ability in Children - Ibrohimova Nasibakhon; Ibrohimjonova Mohlaroyim (Web of Journals Publishing, 2023)
Music education can be conventionally divided into two stages. The first is the preparation stage. The main goal is to develop children's musical skills. During this time, children should learn to distinguish specific features of musical sounds, such as pitch and duration, and prepare to learn musical notation. At the second stage, one begins to learn musical notation, that is, the direct representation of musical sounds in a graphic way - musical notation. In the process of music training, the child perceives the reality of life through musical images. Musical works suitable for children's age leave an unforgettable impression on children and enrich their spiritual world. In this article, you can get acquainted with the information about determining the musical ability of children and developing their ability.
Keywords: music, ability, determination of ability, methodology, work on oneself, genetic factors, social factors.